Tuning phase compositions of MoS2 nanomaterials for enhanced heavy metal removal: performance and mechanism. Issue 21 (24th May 2022) - Han, Qi; Cao, Hao; Sun, Yuchen; Wang, Gang; Poon, Sidney; Wang, Monong; Liu, Bei; Wang, Yanggang; Wang, Zhongying; Mi, Baoxia
Abstract : The remediation performance of 2D MoS2 nanomaterials in the heavy-metal-containing solutions is closely correlated with the phase composition of the materials. Abstract : Two-dimensional MoS2 nanosheets have shown great potential in heavy metal remediation due to their unique properties. MoS2 has two primary phases: 1T and 2H. Each has different physiochemical properties, but the impact of these differences on the overall material's heavy metal removal performance and associated mechanisms is rarely reported. In this study, we synthesized morphologically similar but phase-distinct MoS2 samples via hydrothermal synthesis, which comprised dominantly either a metallic 1T phase or a semiconducting 2H phase. 1T-MoS2 samples exhibited higher removal capacities for Ag + and Pb 2+ cations relative to 2H-MoS2 . In particular, an eight-fold increase in the Pb 2+ adsorption capacity was observed in the 1T-MoS2 samples ( i.e. ∼632.9 mg g −1 ) compared to the 2H-MoS2 samples (∼81.6 mg g −1 ). The mechanisms driving the enhanced performance of 1T-MoS2 were investigated through detailed characterization of metal-laden MoS2 samples and DFT modelling. We found that 1T-MoS2 intrinsically had a larger interlayer spacing than 2H-MoS2 because water molecules were retained between the hydrophilic 1T nanosheets during hydrothermal synthesis. The widened interlayer spacing in 1T-MoS2 allowed the diffusion of heavy metal ions into the nanochannels, increasing the number of adsorption sites and total removal capacities. On the other hand, DFT modelling revealed the energy-favorable adsorption complex of Ag + and Pb 2+ for 1T-MoS2, in which each metal atom was bonded with three S atoms leading to much higher adsorption energies relative to 2H-MoS2 for Ag + and Pb 2+ . This study unravels the underlying mechanisms of phase-dependent heavy metal remediation by MoS2 nanosheets, providing an important guide for the use of 2D nanomaterials in environmental applications which include heavy metal removal, contaminant sensing, and membrane separation.